The expression and clinical significance of miR-30b-3p and miR-125b-1-3p in patients with periodontitis - Jinjuan Zhu; Zhihong Zhong (BMC, 2022)
Abstract Objective Periodontitis is a chronic inflammatory infectious disease caused by the deposition of dental plaque on the tooth surface, leading to adverse systemic consequences. Accumulating evidence shows that dysregulated microRNAs (miRNAs) are associated with the disease severity of periodontitis. Herein, we report two novel miRNAs, miR-30b-3p and miR-125b-1-3p, in the context of periodontitis and their relationships with disease severity of periodontitis. Methods The miRNA profiles of gingival crevicular fluid (GCF) samples were used to screen differentially expressed miRNAs (DEmiRNAs) between periodontitis patients and periodontally healthy individuals. Clinical human GCF samples were collected from 80 patients diagnosed with periodontitis (PD +) for the first time and 100 periodontally healthy individuals (PD-). The severity of periodontitis was categorized into mild/moderate (MPD) and severe (SPD) groups. The expressions of miR-30b-3p and miR-125b-1-3p were determined by quantitative real-time PCR. The levels of IL-1β, IL-6, and TNF-α were determined by ELISA methods. Results We applied GEO2R bioinformatics tool to analyze the raw data of the GSE89081 dataset and identified miR-30b-3p (|logFC|= 1.987) and miR-125b-1-3p (|logFC|= 1.878) between periodontitis patients and periodontally healthy individuals. It was found that PPD, CAL, BOP, and the relative expression levels of miR-30b-3p and miR-125b-1-3p were all higher in the PD + group than the PD- group, in the SPD group than the MPD group (P < 0.05). The periodontitis patients with high-miR-30b-3p expression exhibited increased PPD, CAL, and BOP compared to those low-miR-30b-3p expression, while high-miR-125b-1-3p expression group showed significant differences on PPD and BOP from low-miR-125b-1-3p expression group (P < 0.05). Pearson correlation analysis demonstrated a significantly positive correlation between the levels of inflammatory cytokines, miR-30b-3p expression, and miR-125b-1-3p expression (P < 0.001). Results of ROC curves showed AUC of 0.878 and 0.927, sensitivity of 0.843 and 0.855, and specificity of 0.791 and 0.801, respectively, when miR-30b-3p and miR-125b-1-3p expression levels were used to diagnose periodontitis. Conclusion These data unveiled that miR-30b-3p and miR-125b-1-3p expressions may be associated with the pathogenesis of periodontitis.